The performance of locally produced xanthan gum in drilling mud - Ismail, I.; Lim, P. S. (Faculty of Chemical Engineering & Natural Resources, 2008)
Xanthan gum is one of the important mud additives nowadays which acts as viscosifier. Currently, Malaysia oilfields mainly are using imported xanthan gum from China, which is very expensive due to towering demand. Therefore, this research project focused on the performance of locally produced xanthan gum in drilling fluid. Laboratory works conducted were mainly on the rheological properties, API fluid-loss, and the pyruvate content test. The experimental results revealed that the locally produced xanthan gum could not match the performance of Flowzan.